Clinical and ultrasound characteristics of vaginal lesions. Issue 1 (January 2021) - Pozzati, Federica; Moro, Francesca; Leombroni, Martina; Bertoldo, Valentina; Trivellizzi, Nausica; Mascilini, Floriana; Bolomini, Giulia; Ciccarone, Francesca; Garganese, Giorgia; Scambia, Giovanni; Testa, Antonia Carla
Abstract : Objective : Ultrasound examination represents the most important diagnostic method to preoperatively assess gynecological diseases. However, the ultrasound characteristics of vaginal pathologies are poorly investigated. The aim of this study was to describe the clinical and ultrasound characteristics of vaginal lesions detected at ultrasound. Methods : This was a single center, prospective, observational study including patients with vaginal masses examined from January 2017 to May 2019. Morphologic sonographic characteristics of the lesions were described as unilocular, multilocular, unilocular‐solid, multilocular‐solid, and solid. For the analysis, patients were grouped into a 'malignant group', including patients with confirmed malignancy at final histology, and a 'benign group', including patients with a confirmed benign pathology at final histology and patients without a histological diagnosis but with a lesion that manifested no changes during follow‐up. Results : 44 patients were enrolled. 22 (50%) of 44 lesions were benign: 12 (54.5%) of these underwent ultrasound follow‐up and did not show any changes at the 12 month follow‐up whereas 10 (45.5%) lesions had surgical excision which confirmed the benign nature. The remaining 22 (50%) of 44 lesions underwent surgery because of suspicion of malignancy: histology confirmed a malignancy in 20 (90.9%) of 22 cases. Benign lesions were described as follow: 11/24 (45.8%) unilocular, 3/24 (12.5%) multilocular with two locules, and 10/24 (41.7%) solid lesions. Malignant lesions were solid in 19/20 (95%) cases and multilocular‐solid in 1/20 (5%). Most benign lesions had a color score of 1‐2 (20/24, 83.4%) while malignant lesions had a color score of 3‐4 (18/20, 90%). Conclusion : A typical ultrasound image of a benign lesion was a unilocular cyst or hypoechoic solid mass with no or minimal vascularization on color Doppler examination. Malignant vaginal lesions were hypoechoic solid tumors with irregular margins and moderate/rich vascularization or multilocular‐solid. Ultrasound should be used to supplement the clinician in the management of vaginal lesions.